1982
DOI: 10.1111/j.1365-2141.1982.tb01941.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemostatic and rheological changes in normal pregnancy and pre‐eclampsia

Abstract: Platelet activity (microaggregate formation, ADP-aggregation and beta-thromboglobulin release), coagulation activity (fibrinogen level and factor VIII related antigen/coagulant activity), and rheological factors (plasma viscosity, whole-blood viscosity and erythrocyte deformability) were studied serially in 14 healthy pregnancies to determine the effect of gestational age. Fourteen patients with pre-eclampsia, each matched for stage of gestation with a normal pregnancy, showed normal rheology of circulating bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1
1

Year Published

1983
1983
1996
1996

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 25 publications
4
28
1
1
Order By: Relevance
“…Some investigators found increased aggregability to ADP and adrenaline during pregnancy. 21,27,41 Our results disagree with these observations, since the aggregation responses to ADP, adrenaline, arachidonic acid, collagen, and ristocetin were significantly lower during pregnancy compared to nonpregnant controls. In contrast, other investigators could not establish any differences between pregnant and nonpregnant women.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Some investigators found increased aggregability to ADP and adrenaline during pregnancy. 21,27,41 Our results disagree with these observations, since the aggregation responses to ADP, adrenaline, arachidonic acid, collagen, and ristocetin were significantly lower during pregnancy compared to nonpregnant controls. In contrast, other investigators could not establish any differences between pregnant and nonpregnant women.…”
Section: Discussioncontrasting
confidence: 57%
“…Reports on platelet count in pregnancy have provided discordant results. In most studies, no significant changes were observed, 11,15,21,26,27 while in others, like our own, a slight reduction was found. 15,28,29 In contrast to these findings, Mor et al 30 found a marked and progressive increase in the platelet count during pregnancy and a sharp drop at the time of placental delivery.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Plasma levels of fibrinogen are related to physiological factors: race [13], gender [14], age [15], pregnancy [16], menopause [17], to lifestyle and environmental factors: smoking [18], body weight [19], stress [20], social class [21], alcohol intake, exercise [22], season [23] and to pathological conditions, mainly inflammatory status. The genetic contribution to the plasma level of fibrinogen is estimated to range between 20 [24] the consequence of an acute-phase reaction, whereas oth er proteins like C-reactive protein can increase more than hundred-fold under similar cytokine stimulation (IL-6, IL-ip, TNF-a) [27,28].…”
Section: W Hat Regulates the Plasm A Level Of Fibrinogen?mentioning
confidence: 99%
“…Many situations have recently proven to be associated with the presence of inelastic, only slightly deformable 'dangerous red cells', through still undefined alterations in the relationship between the membrane structures or in the intracytoplasmatic constituents: preeclampsia [85][86][87], hypertension [88][89][90][91], diabetes [92][93][94][95], hyperlipi demia [96,97], hyperfibrinogenemia [79,96], hyposideremia [98], vitamin E deficiency [99], and acidosis [100].…”
Section: Hemorrheological Approachmentioning
confidence: 99%